Sistema de gestión de marca ciudad para incrementar el turismo interno hacia la ciudad de Huamachuco. - Castillo Ramos, Fany Natali (2012)
This work entitled City Brand Management System to increment domestic tourism to the city of Huamachuco, intends to describe how to increment domestic tourism towards Huamachuco, having as main objective to develop a management system of “Huamachuco City Brand”. The population consisted of men and woman aged 18 to 62 years old, using simple random sampling, with a sample of 369 domestic tourists. Data collection was conducted through quantitative techniques such as surveys and quantitative techniques such as simple observation and interviews. The study results indicated that most of the domestic tourist INDEED find it necessary to create a city brand that identifies the city of Huamachuco, and that this mark will increment domestic tourism to the city, highlighting the cultural and environmental identity, through advertising media such as television and the I radiate. One of the main conclusions that we have reached in this work is that the development of Huamachuco City Brand highlighting the cultural identity, focused mainly on the archaeological remains and the traditional dance “Los Incas”, and the environmental identity, focused on the main square of the city, which will increment domestic tourism to the city of Huamachuco.